Election campaign: definition and temporal boundaries - Evgeniy M. Korovin (Правоприменение, 2020)
The subject. Detection of the essence of electoral process, the election campaign and their influence on the temporal component of the electoral process is the subject of this publication.The purpose of the article is to confirm or disprove hypothesis that the concept of "election campaign" should include activities for the preparation and conduct of elections, carried out in the period from the date of the decision on the appointment of elections to the day of official publication (publication) of the decision on the results of electionsThe methodology. General scientific methods were used when considering and analyzing the concepts of the electoral process, election companies, and stages of the electoral process. Normative-logical and comparative-legal methods were used in the process of analyzing the electoral legislation.The main results and scope of their application. The definition of the electoral process is considered by scientists not only as a system of relations, but also as a phenomenon, as an institution, as a form of implementation of constitutional principles, as a legal technology, as a technological infrastructure. Almost all authors, detecting the essence of the electoral process, cannot avoid the temporal aspect of this phenomenon. Political scientists and sociologists understand an election (election) campaign as a system of various campaigning events, with the help of which political parties and individual candidates seek the support of voters in elections. The election campaign in the broad sense is the period of time during which citizens have the opportunity to exercise most of their electoral rights. It is essential not only to legislate consolidation of the definition of “election campaign”, but also to define its temporal component, adequate to the goals and objectives of the implementation of the constitutional right to elect and to be elected.The current law defines the election campaign as activities for the preparation and conduct of elections from the date of publication of the announcement of elections until the day the election commission submits the election report.The start of the election campaign is given by the publication of the announcement of the election, but not the adoption of this decision. The campaign ends not with the determination of the winner, but after the election commission submits a report on budget spending, i. e. 3 months after the actual completion of the election. This duration of the campaign does not correspond to the objectives of the election and artificially lengthens the election campaign.The time limits of an election campaign are closely related to the stages of the electoral process, i.e., a set of electoral actions and procedures that are separate in time, aimed at forming a government body and electing an official. The author refers to the mandatory stages of the electoral process as determining the voting day and publishing the decision to call elections; nominating and registering candidates (lists of candidates); election campaigning; voting, determining the results of voting, determining the results of elections and publishing them. Deadlines mark the boundaries of the stages of the electoral process, affecting its institutional, subject and technological components.Conclusions. Nowadays, it is necessary to reduce the legislatively fixed period of the election campaign and, as a result, clarify the definition of “election campaign”, which is preferably defined as activities for the preparation and conduct of elections, carried out from the date of the decision of the authority or official on the election to be held until the day official publication of the decision of the election commission on the election results.